STUDENTS’ INDUSTRIAL WORK EXPERIENCE SCHEME (SIWES): FUNDAMENTAL LINTEL FOR PROSPECTIVE ENTREPRENEURS - Israel-Regha, Mercy N (PEOPLE: International Journal of Social Sciences, 2015)
With a greater belief in a universal basis of principles underlying management processes, institutions of higher learning in Nigeria have ventured into what is regarded as necessary for effective solution to practical business problems. This article assesses the prospect of the strategies adopted by institutions of higher learning on entrepreneurship education to boost business enterprises in Nigeria. The study employed a survey design to examine approaches to effective guide for learning entrepreneurship courses in three levels of institutions of higher learning. A structured questionnaire was used to generate data on the prospect of the approaches from 450 students from the 3 institutions. The reliability coefficient of the instrument yielded .69 with Guttmann Split half. Two research questions were answered from a weighted mean benchmark of 2.50 and above for anticipation and less for implausible. The results showed that the institutions adopted similar approaches, Universities, Polytechnics and Colleges of education exposed their learners to a compulsory industrial attachment to consolidate the classroom experience but on different duration. It is recommended that all students of entrepreneurship education be fixed up with public firms during every long vacation throughout their study duration. A vacation skill acquisition report of the learners should form 50% of the assessment in relevant courses. All certified intending entrepreneurs should be aided to start on a strong financial foundation from budgetary allocation of the state.